Peningkatan Pengetahuan Gizi Pada Siswa Sekolah Dasar Negeri Tanah Putih Sebagai Upaya Pencegahan Malnutrisi - Grouse Oematan; Christin Nabuasa; Eryc Haba Bunga; Grace Maku; Mega Liufeto; Yudishinta Missa (UKInstitute, 2023)
Children are an integral part of national development. In the future children will play a role as the next generation of the nation that determines its quality. School-age is a phase where growth and development occur very quickly, to be able to achieve optimal growth and development, an adequate intake of nutrients is necessary. However, the fulfillment of nutrients in this age group is often not properly met. This condition happens because of many factors, one of them is that children have a low level of knowledge and understanding about nutrition. The nutrition counseling activity was attended by 80 students. The activities are effective in increasing children’s knowledge and understanding of the importance of balanced nutrition. If the material was presented in an interesting form, accompanied by animated video, it will increase the enthusiasm of students in receiving information. In addition, the existence of a balanced nutrition pocket book for students helped them to understand the importance of balanced nutrition.